My experience leading NASA SporeSat: a lab-on-chip device for single-cell study - Wan Salim, Wan Wardatul Amani (2019)
A lecture to the public for Minggu Sains Negara (MESTECC) at Melaka International Trade Centre (MITC), Ayer Keroh, Melaka